Modern weapons and military equipment for issue 1-2016 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Specialist equipment of members of the Russian special force Department "A": Overview of special equipment and weaponry at the disposal of the Russian elite anti-terrorist unit. Construction Standards of Modern Infantry Specialist Weapons.